Nurses’ Knowledge, Attitude, and Practice Regarding Sexual Health Care for Cancer Patients: A Systematic Review - Susiladewi, Ida Ayu Md Vera; Afiyanti, Yati; Rahman, La Ode Abdul (Jurnal Ners, 2025)
Introduction: Cancer and its treatments negatively affect patient sexual health. However, this aspect is often neglected in cancer care. As holistic care providers, nurses have a pivotal role in addressing their patient’s sexual health problems. This study aims to summarize what is currently known about nurses’ knowledge, attitude, and practice when helping cancer patients with concerns regarding their sexual health and recent educational strategies to enhance the nurses’ competencies in relation to cancer patients’ sexual healthcare. Methods: The authors conducted a systematic review using PRISMA 2020 Guidelines. The articles were derived from five electronic databases (Scopus, Science Direct, ProQuest, MEDLINE, and PubMed), consisting of full text original research articles published between 2015 and 2024 using quantitative, qualitative or mixed methods. Review articles, books, and book chapters are excluded. Results: The initial search resulted in 1,126 articles. Thirteen articles that met the selection criteria were included due to having good methodological quality. The nurses’ knowledge, attitude, and practice toward sexual healthcare was found to be moderate. Nurses argued that they need specific knowledge and skills to confidently address sexuality problems among their patients. Educational interventions were effective at helping to improve the nurses’ knowledge, attitude, and skills on sexual health care provision. Conclusion: Institutional and educational support are important factors for mastering the nurses' ability to provide comprehensive sexual healthcare. A clear policy, sufficient facilities and comprehensive strategies are needed to mediate consistent cancer patient sexual healthcare provisions.